Pemahaman Mendalam Terkait Kata Al Fitnatu dalam Tafsir Q.S. Al Baqarah Ayat 191 - Ismiati; Fuad Fansuri (Universitas Majalengka, 2024)
The research aims to explore the words Al Fitnatu in Q.S. al-Baqarah verse 191, the author highlights the lafaz Al Fitnatu which is interpreted as fitnah. Looking at the socio-historical conditions in the books of Tafsir, it is certainly not in accordance with the current understanding (Indonesian society). The purpose of this research is to find out the meaning of Al Fitnatu in the Qur'an, while the research method that the author uses is descriptive analysis method by using library data, so this research is library research. The results of this study are that Al Fitnatu in the context of tafsir means shirk and kufr, a disaster that will plunge into hell. While the misunderstanding of the meaning of the word fitnah in the context of Indonesian society is more due to the simplification or oversimplification of the meaning of the word fitnah in Arabic. The word fitnah in Indonesian is unable to accommodate the meaning contained in Arabic.